Success Depends on the Animals : Emigrants, Livestock, and Wild Animals on the Overland Trails, 1840-1869 - Ahmad, Diana L., 1953- (Book collections on Project MUSE., 2016)
"Between the 1840s and 1860s, thousands of emigrants crossed the Great Plains to California, Oregon, and Utah. They learned how to deal with many new situations, including how to work with the animals they brought with them on the journey. Although many emigrants knew how to take care of the livestock on their family farms, travel on the overland trails forced them to look at their animals in a different light as their lives now depended on their livestock in an unprecedented way. Many of the emigrants had never ridden a horse before, let alone hitched an ox to a wagon filled with the family's possessions, or relied upon a mule to get them through the deserts and over the mountains. The travelers also encountered wild animals new to them, such as buffalo and prairie dogs. The emigrants sometimes even attributed human characteristics to the animals. Prior to leaving their homes, the travelers had been told by the philosophers that animals were little more than beasts of burden and some ministers said that caring for the animals took time away from God. Despite that, the sentimental literature of the era encouraged the overlanders to treat their animals well and the humans would be repaid by how the animals helped the emigrants achieve their goals. Unexpectedly, many emigrants often befriended the domestic, as well as the wild animals, along the way and by the end of the trail, humans and animals alike had become overlanders"--Provided by publisher.